Current Topics in Anemia 2018
DOI: 10.5772/intechopen.69048
|View full text |Cite
|
Sign up to set email alerts
|

Iron Deficiency Anaemia

Abstract: Iron deficiency anaemia as the most common nutrition disorder has only marginal reduction globally during recent decades, with the highest burden in pregnant women and young children. Insufficient iron storage and/or excessive loss of iron are common causes of iron deficiency anaemia. Therefore, understanding the complexity of the regulatory network required to maintain iron homeostasis and identifying the functional variants associated with iron metabolism should be fundamental and crucial to control and trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 105 publications
0
8
0
Order By: Relevance
“…Neonatal deaths stem from poor maternal health, inadequate nutritional status [16][17][18], or care during pregnancy [9,10,14,35]. Although no association was identified with maternal age, antenatal care visit, gravidity, and obstetric complications similar to other study [8], the high prevalence of neonatal mortality attributed to LBW may be a sign of poor maternal conditions [9,10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neonatal deaths stem from poor maternal health, inadequate nutritional status [16][17][18], or care during pregnancy [9,10,14,35]. Although no association was identified with maternal age, antenatal care visit, gravidity, and obstetric complications similar to other study [8], the high prevalence of neonatal mortality attributed to LBW may be a sign of poor maternal conditions [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Preterm births are at high risk of RDS due to pulmonary surfactant deficiency in the lungs and are prone to hospital admission and death [12,13,29,30]. Several interlinked factors could have resulted for this up surge in LBW babies, such as in-utero growth restriction associated with poor nutritional status of mothers of secondary to low socio-economic status [9,10,[16][17][18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, IV supplementation can reduce the risk of gastrointestinal toxicity, avoid oxidative damage to the intestinal mucosa, with a rapid increase in Hb, and will be positively correlated with increasing serum hepcidin levels. (11) (25) Zehra (2017) found that intravenous iron supplementation causes an increase in hepcidin levels. Iron deficiency anemia is associated with low serum hepcidin levels.…”
Section: Discussionmentioning
confidence: 99%
“…It is a common disease among women, children, and the elderly. It is also associated with many medical conditions and thus complicates the differential diagnosis [17][18][19][20]. This study was conducted to create a new approach that could help hematologists and physicians identify a group of thalassemic patients and SCD patients from IDA and normal subjects.…”
Section: Discussionmentioning
confidence: 99%